Discussion on the Reconstruction of Electrical Engineering Undergraduate Teaching Scheme Facing the New Generation Power System - Gong, Wangyang; Deng, Feng; Wang, Xuhong; Chen, Fangfang (Frontiers in Energy Research, 2022)
With the construction of a new generation of electric power systems with new energy as the main body, there are major changes in the traditional electrical engineering undergraduate teaching system. On the one hand, the dynamic operating characteristics of the power system dominated by new energy sources and dominated by power electronic equipment will be significantly different from the traditional power system dominated by synchronous generators. Therefore, there is an urgent need to reform the curriculum system to train electrical engineering professionals who can adapt to the future development trend of the power system. On the other hand, with the rapid advancement of advanced information technology in recent years, the application of cutting-edge technologies such as cloud computing, big data, and artificial intelligence in the field of electrical engineering has become more and more in-depth. Therefore, there is an urgent need to cultivate advanced technical experts who possess more advanced information theory and cybernetics knowledge and master the application of cutting-edge information technology in the field of electrical engineering. From the perspective of student training and professional construction needs, this paper systematically analyzes the lag of the traditional electrical engineering curriculum system, and analyzes the knowledge needs of electrical engineering students adapting to the development of the new generation of power systems. From the perspective of teaching schemes, curriculum systems, and evaluation systems, a plan for restructuring the teaching system was proposed. The work in this article can provide a reference for the training of college students majoring in electrical engineering, and it can also provide a more feasible improvement idea for the training of college students in other majors.